SOCIAL AND SPIRITUAL REFORMS IMPLEMENTED IN NEW UZBEKISTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article focuses on the issues of building a new Uzbekistan in line with world standards, implementing fundamental reforms in the political, economic, social and spiritual spheres, creating a legal system that will strengthen them with the law.